Expanding the Lexicon Linguistic Innovation, Morphological Productivity, and Ludicity - Arndt-Lappe, Sabine; Braun, Angelika; Moulin, Claudine (The Dynamics of Wordplay, 2018)
The book series is dedicated to the study of the multifaceted dynamics of wordplay as an interface phenomenon. The contributions aim to bring together approaches from various disciplines and present case studies on different communicative settings, including everyday language and literary communication, and thus offer fresh perspectives on wordplay in the context of linguistic innovation, language contact, and speaker-hearer-interaction.